Appraising Breakthrough Action Organisation’s Social and Behavioural Change Communication in the “Check Am O!” Tuberculosis Campaign in Nasarawa State - Ogili, Maryann Ukamaka; Anshase, Mercy Tartsea; Moses, Akurega Iorhemba (Darul Yasin Al Sys, 2025)
This study examined the effectiveness of Breakthrough Action’s social and behaviour change communication (SBCC) campaign titled “Check Am O!” on tuberculosis (TB) awareness and behavioural response among residents of Nasarawa State, Nigeria. Adopting a survey research design, data were collected using structured questionnaires administered to a sample of 400 respondents, determined using Yamane’s (1967) formula from a projected population of 2,946,138. A multistage sampling technique was employed to ensure representativeness. The study was anchored on the Knowledge, Attitude, and Practice (KAP) theory, and data were analyzed using the Pearson Product Moment Correlation Coefficient (PPMC) at a 0.05 alpha level. The findings established a statistically significant relationship between residents’ knowledge of TB, their attitudes, and the adoption of recommended health behaviours as promoted in the “Check Am O!” campaign. Respondents demonstrated high awareness of TB risks (WMS = 4.43), and this knowledge positively influenced their adoption of precautionary measures (WMS = 4.22). The study concluded that the campaign effectively influenced knowledge, attitude, and behavioural change regarding TB prevention. It recommended the inclusion of diverse folk and indigenous media platforms to enhance message penetration, particularly in peri-urban and rural areas, ensuring equitable access to campaign information across all communities in Nasarawa State.